Isolation and Functional Analysis of the DhMYB2 and DhbHLH1 Promoters from Phalaenopsis-Type Dendrobium Involved in Stress Responses and Tissue-Specific Expression - Yachen Wang; Chonghui Li; Wenjuan Zhu; Yamei Li; Xiqiang Song; Junmei Yin (Horticulturae)
Phalaenopsis-type Dendrobium (Den-Phals) is a commercially valuable orchid, with floral color being key to its market appeal. Despite the significance of anthocyanin biosynthesis in color development, its transcriptional regulation in Den-Phals remains unclear. This study functionally characterized the promoters of DhMYB2 and DhbHLH1, two key transcription factors involved in anthocyanin biosynthesis. A 1864 bp DhMYB2 promoter and a 1995 bp DhbHLH1 promoter were isolated using genome walking. Bioinformatics analysis identified cis-acting elements associated with abiotic stress responses, phytohormone signaling, and floral-specific regulation. 5′-Deletion analysis in tobacco leaves identified core regulatory regions for the DhMYB2 promoter (−1864 to −937 bp) and DhbHLH1 promoter (−1995 to −924 bp). GUS staining and activity assays demonstrated that the activities of the DhMYB2 and DhbHLH1 promoters were significantly increased under treatments of long light, low temperature, drought, salicylic acid (SA), and abscisic acid (ABA), while the DhbHLH1 promoter was also induced by methyl jasmonate (MeJA) and indole-3-acetic acid (IAA). Furthermore, promoter activity of DhMYB2 and DhbHLH1 was detected only in transgenic Arabidopsis flowers, suggesting that these promoters exhibit floral-specific activity. This study provides the first functional analysis of Den-Phals anthocyanin promoters, revealing their stress-responsive nature and floral specificity, which will facilitate molecular breeding of novel orchid cultivars.